The Relationship Between Self-Efficacy and Students Academik Procrastination - Wulandari, Wulandari; Ardi, Zadrian (Jurnal Aplikasi IPTEK Indonesia, 2021)
This research is motivated by the phenomenon of increased academic procrastination among students. Students carry out academic procrastination or delay in working on or completing academic assignments. One of the causes of academic procrastination is self-efficacy. This study aims to: (1) describe students self-efficacy, (2) describe students academic procrastination, (3) to test whether there is a relationship between self-efficacy and student academic procrastination. This study uses a quantitative approach with correlational tioe. The subjects of this study were 613 students with a sample of 244 students. The sampling technique is Stratified Random Sampling. The data collection tool uses a questionnaire instrument with a Likert scale. The data analysis technique used is descriptive statistical techniques and pearson product moment techniques. The research findings show that: (1) self-efficacy is in the high category, (2) academic procrastination is in the high category, (3) there is a significant negative relationship between self-efficacy and student academic procrastination, with a correlation coefficient of 0.413, a significance of 0.000 . Based on the research results, it is expected that guidance and counseling teachers can provide assistance in the form of information guidance services, group guidance services, so as to be able to improve self-efficacy properly.